2013
DOI: 10.1007/s12663-013-0533-4
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Study of Prevalence of Systemic Diseases in Oral Maxillofacial Surgery Patients of Central India

Abstract: The aim of study was to evaluate prevalence of systemic disease in oral surgery patients of central India which is 4.055 % with highest population showing involvement of cardiovascular disease and minimum population undergoing oral surgical procedures are compromised by various infectious diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 4 publications
0
12
1
1
Order By: Relevance
“…The findings of this study showed that 41.4% of the patients referring to the Oral and Maxillofacial Medicine Department of the Dental Branch of Islamic Azad University of Tehran in 2016-17 had systemic conditions and diseases, which is very close to the findings of research by Al-Bayaty et al in West Indies (42%), (12) Mesgarzadeh et al in Tehran (41%), (10) Parirokh et al in Kerman, Mashhad, and Tehran (33.8%), (14) and Ayazi and Esfahani in Qazvin (32.5%) in the range of 30-50%. (1) In research by Khader et al in Northern Jordan (58.6%), (3) Amirchaghmaghi et al in Mashhad (73.3%), (11) and Kumar and Rajan in South India (52.8%), (5) the prevalence of systemic diseases has been reported to be higher than this range; However, in the three mentioned studies, the studied populations were small, and the studies were conducted over a short period of time; in studies by Kolte et al in Central India (4.05%) (15) and Mohammad et al in Southern Saudi Arabia (10.3%), (4) the prevalence of systemic diseases has been reported to be lower than this range.…”
Section: Discussionmentioning
confidence: 98%
“…The findings of this study showed that 41.4% of the patients referring to the Oral and Maxillofacial Medicine Department of the Dental Branch of Islamic Azad University of Tehran in 2016-17 had systemic conditions and diseases, which is very close to the findings of research by Al-Bayaty et al in West Indies (42%), (12) Mesgarzadeh et al in Tehran (41%), (10) Parirokh et al in Kerman, Mashhad, and Tehran (33.8%), (14) and Ayazi and Esfahani in Qazvin (32.5%) in the range of 30-50%. (1) In research by Khader et al in Northern Jordan (58.6%), (3) Amirchaghmaghi et al in Mashhad (73.3%), (11) and Kumar and Rajan in South India (52.8%), (5) the prevalence of systemic diseases has been reported to be higher than this range; However, in the three mentioned studies, the studied populations were small, and the studies were conducted over a short period of time; in studies by Kolte et al in Central India (4.05%) (15) and Mohammad et al in Southern Saudi Arabia (10.3%), (4) the prevalence of systemic diseases has been reported to be lower than this range.…”
Section: Discussionmentioning
confidence: 98%
“…Despite the high success rate of dental surgeries, some risk factors predispose the occurrence of complications, highlighting the inadequate preparation of professionals and patients. Among the risk factors, special attention should be given to the preoperative preparation of systemically compromised patients [3].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it is possible to observe a higher prevalence of patients with chronic diseases such as diabetes and cardiovascular complications. This is mainly due to the increased life expectancy of the general population, which has become more numerous and seeks dental care with higher frequency [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…el Valor de P= 0.00, afirma que existe una relación de dependencia entre las variables analizadas, esto quiere decir que el tratamiento de extracción, depende o está muy relacionado con el diagnóstico sistémico individual, siendo estadísticamente significativo.Se demostró estadísticamente que existe prevalencia entre los pacientes que fueron sometidos a extracciones simples y las enfermedades sistémicas individuales (p < 0,05), por lo tanto es de gran importancia que los pacientes reporten el padecimiento de estas enfermedades y así evitar posibles complicaciones. Estos resultados concuerdan con lo estudiado por Kolte et al V. 2014,(1) quienes evidenciaron que existía diferencia significativa, demostrado mediante la prueba de chi cuadrado la relación entre prevalencia de enfermedades sistémicas de los pacientes de Cirugía Maxilofacial Oral de la India Central (p < 0,01). Según Medina C et al 2013, (5) varias investigaciones a nivel mundial han comprobado que una posible infección en la cavidad bucal trae consecuencia sobre diferentes enfermedades sistémicas, por esta razón es necesario estar informado si el paciente sufre de alguna de estas enfermedades y en caso de una infección por efecto de una extracción dental se tomen las medidas preventivas y correctivas acorde con la situación.Hernández P. 2012, (6) expresa sobre el manejo de los pacientes con compromiso sistémico, es importante que el odontólogo entienda la patología sistémica del paciente, los diferentes métodos de diagnosticarla y analizar los parámetros que reportan las pruebas de laboratorio en especial los hematológicos y bioquímicos, además del tratamiento que utilizan y las interacciones medicamentosas con los usados durante la extracción dental, como fármacos analgésicos, antimicrobianos y anestésicos.…”
unclassified